Impact of selenium and selenoproteins on idiopathic male infertility: a comprehensive review - Zečević, Nebojša; Šarac, Ivana; Perović, Milan; Zeković, Milica; Stojsavljević, Aleksandar (Frontiers in Nutrition, 2026)
This comprehensive review systematizes the recent literature on the role of selenium (Se) and selenoproteins in male fertility and the mechanisms involved, by integrating data from animal, human, and in vitro studies. Additionally, it gives an overview of human studies published on the Se levels in seminal plasma worldwide, comparison of Se levels in seminal plasma and blood (serum or plasma) between infertile and fertile men, associations between seminal and/or blood Se levels and sperm quality, and elucidates whether Se supplementation could be a sustainable treatment for male infertility. Overall, the findings from studies in experimental and domestic animals, cell cultures, and humans confirm the role of Se and selenoproteins in male fertility, suggesting the multiple mechanisms involved at various levels of the male reproductive system. The studies in humans on Se seminal levels show that, generally, infertile men tend to have lower levels of seminal plasma Se; however, in some cases, significantly higher Se levels have been observed, suggesting that excessive Se may also be linked to infertility. Additionally, most studies demonstrate a positive correlation between Se levels in both seminal plasma and blood with certain seminogram quality parameters, particularly sperm motility. These findings, along with most available clinical trials, support the potential benefits of Se supplementation for improving male infertility. However, there are limited studies on Se status or supplementation concerning in vitro fertilization outcomes and pregnancy, as well as the association of other functional Se-status biomarkers in seminal plasma with infertility. Further studies are needed to define the best Se-status biomarkers related to male fertility, their optimal ranges, analytical techniques for their assessment, and the optimal Se supplementation dosages, formulations, and treatment durations. Additionally, the potential health risks associated with high-dose Se intakes should be carefully considered.